2018
DOI: 10.21511/pmf.07(2).2018.04
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relationship between corruption and development of the Tunisian stock market

Abstract: The aim of this article is to seek especially the impact of corruption on the bond and stock market development. For the methodology/approach, the authors analyze a sample of 20 listed Tunisian firms from the Stock Exchange and Financial market, covering the period from 2006 to 2016 by using pooling cross section techniques. The results find a significant positive effect of the level of corruption on the stock market index and the logarithm of capitalization. This is consistent with the view that corruption ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The regression model shows that the corruption perception index coefficient values are significant at (5%), this finding seems to be consistent with some prior studies which are expected and would satisfy the theoretical viewpoint that high corruption has a negative effect on the stock market due to the investors who are not interested to invest in a corrupted state (Ming et al, 2018;Ojeka et al, 2019). Nevertheless, the study results about corruption are not similar to some other past studies which reveal that the level of corruption is precipitated and speeds up the business and economic growth (Aljazaerli et al, 2016;Shahbaz et al, 2003;Missaoui et al, 2018). Hence the study cannot reject the first hypothesis.…”
Section: Descriptive Statisticssupporting
confidence: 84%
See 3 more Smart Citations
“…The regression model shows that the corruption perception index coefficient values are significant at (5%), this finding seems to be consistent with some prior studies which are expected and would satisfy the theoretical viewpoint that high corruption has a negative effect on the stock market due to the investors who are not interested to invest in a corrupted state (Ming et al, 2018;Ojeka et al, 2019). Nevertheless, the study results about corruption are not similar to some other past studies which reveal that the level of corruption is precipitated and speeds up the business and economic growth (Aljazaerli et al, 2016;Shahbaz et al, 2003;Missaoui et al, 2018). Hence the study cannot reject the first hypothesis.…”
Section: Descriptive Statisticssupporting
confidence: 84%
“…On contrary, numerous studies support the viewpoint of precipitation of corruption, speeding the business and economic growth (Missaoui et al, 2018). A study clarified a significant positive influence of corruption level on the stock market for a sample of (20) listed companies for the period (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) (Aljazaerli et al, 2016;Missaoui et al, 2018). In addition, another study focused on Gulf Cooperation Council (GCC) as a special case of relatively high level of corruption for the period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011), as the findings show a positive influence of corruption on stock market development, which is consistent with the view that corruption can speed up the progress of transactions and stimulate the economy (Aljazaerli et al, 2016).…”
Section: Corruption and Stock Marketmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that extreme bureaucracy and complex bank loan paperwork drives entrepreneurs towards providing bribes and corrupted activities which is creating barriers for easy access to bank finance. The same situation is observed at the financial market as well (Missaoui et al, 2018).That's why there is a need in some measures against possible acts of corruption, for example, implementation of the Code of Ethics for SMEs (Antoniuk et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 74%